Głos Olgi Tokarczuk w Bułgarii, czyli jak odnaleźć zgubioną duszę - Grigorova, Margreta (Postscriptum Polonistyczne, 2020)
The text presents aspects of Olga Tokarczuk’s Bulgarian reception: translations, interviews, Bulgarian contacts, and an overview of her visit to Bulgaria in 2014. Special attention was paid to her creative friendship with Georgi Gospodinov. The Bulgarian initiatives related to Tokarczuk’s Nobel Year are presented, including the publication of the wonderful book The Lost Soul, the second edition of the novel Flights and a series of publications in the press.